Universal HIV screening of pregnant women in England: cost effectiveness analysis. Issue 7199 (19th June 1999) - Postma, M J; Beck, E J; Mandalia, S; Sherr, L; Walters, M D S; Houweling, H; Jager, J C
Abstract: Objective: To estimate the cost effectiveness of universal, voluntary HIV screening of pregnant women in England Design: Cost effectiveness analysis. Cost estimates of caring for HIV positive children were based on the stage of HIV infection and calculated using data obtained from a London hospital between 1986 and 1996. These were combined with estimates of the health benefits and costs of antenatal screening so that the cost effectiveness of universal, voluntary antenatal screening for HIV infection in England could be estimated. Main outcome measures: Lifetime, direct costs of medical care of childhood HIV infection; life years gained as a result of the screening programme; net cost per life year gained for different pretest counselling costs; and different prevalence rates of pregnant women who were unaware that they were HIV positive. Results: Estimated direct lifetime medical and social care costs of childhood HIV infection were £178 300 using a 5% discount rate for time preference (1995-6 prices). In high prevalence areas screening pregnant women for HIV is estimated to be a cost effective intervention with a net cost of less than £4000 for each life year gained. For areas with comparatively low prevalence rates, cost effectiveness could be less than £20 000 per life year gained, depending on the number of pregnant women who are unaware that they are infected and local screening costs Conclusions: Our results confirm recent recommendations that universal, voluntary antenatal HIV screening should be implemented in the London area. Serious consideration of the policy should be given for other areas in England depending on local prevalence and screening costs.